Diagnostic upgrade of atypical ductal hyperplasia of the breast based on evaluation of histopathological features and calcification on core needle biopsy. Issue 3 (16th July 2019) - Chen, Lin‐Ying; Hu, Jintao; Tsang, Julia Y S; Lee, Michelle A; Ni, Yun‐Bi; Chan, Siu‐Ki; Tse, Gary M K
Abstract : Aims: Atypical ductal hyperplasia (ADH) of breast is increasingly diagnosed in core needle biopsy (CNB). As higher‐grade lesions were found in the excision in a substantial proportion of ADH on CNB, factors predicting risk of subsequent upgrade are clinically significant. This study aims to investigate relevant histopathological factors in CNB that could predict diagnostic upgrade at excision. Methods and results: One hundred and forty‐three cases of CNB with paired subsequent excision were evaluated for multiple clinicopathological parameters related to CNB sampling, ADH morphology, calcification and other co‐existing histological features, and which of these parameters were associated with diagnostic upgrade at subsequent excisions were determined. Forty‐eight cases (34.3%) were upgraded to malignancy, including 15 invasive cancers and 33 ductal carcinomas in situ (DCIS). An increased tissue area occupied by ADH ( P  = 0.026), a higher number of ADH foci ( P  = 0.004), the presence of solid pattern ( P  = 0.037) and older age ( P  = 0.012) were positively associated with upgrade, while negative associations were found with the presence of micropapillary pattern ( P  = 0.025), co‐existing columnar cell lesions (CCL) ( P  = 0.001) and the presence of calcifications ( P  = 0.009). Multivariate logistic regression analysis showed that the number of ADH foci (HR = 2.810, P  = 0.013) was an independent positive predictor, while co‐existing CCL (HR = 0.391, P  = 0.013) was an independent negative predictor for upgrade. Conclusions: Patients with ADH in CNB showing the presence of co‐existing CCL and a lower number of ADH foci have a lower risk of disease upgrade at excision, and are potential candidates for observation‐only management.